TBX2 expression is regulated by PAX3 in the melanocyte lineage - Liu, Fang (2012)
The paired box homeotic gene 3 (PAX3) is a crucial regulator for the maintenance of melanocytic progenitor cells and has a poorly defined role in melanoma. To understand how PAX3 affects melanocyte and melanoma proliferation, we identified potential PAX3 downstream targets through gene expression profiling. Here we identify TBX2, a key developmental regulator of cell identity and an anti-senescence factor in melanoma, as a directly regulated PAX3 target. We also found that TBX2 is involved in the survival of melanoma cells, and is overexpressed in some melanoma specimens. The identification of TBX2 as a target for PAX3 provides a key insight into how PAX3 may contribute to melanoma evolution and may provide opportunities for pro-senescence therapeutic intervention aimed at disrupting the ability of PAX3 to regulate TBX2.